Colon-targeted dexamethasone microcrystals with pH-sensitive chitosan/alginate/Eudragit S multilayers for the treatment of inflammatory bowel disease. (15th October 2018) - Oshi, Murtada A.; Naeem, Muhammad; Bae, Junhwan; Kim, Jihyun; Lee, Juho; Hasan, Nurhasni; Kim, Wooseong; Im, Eunok; Jung, Yunjin; Yoo, Jin-Wook
Highlights: Dexamethasone microcrystals with colon-targeted chitosan/alginate/Eudragit S multilayers were fabricated. Unwanted burst release of dexamethasone was prevented in the upper gastrointestinal tract pH. Dexamethasone was released in a sustained manner after reaching the colonic pH. Excellent therapeutic activity was found in a mouse model of colitis. Abstract: Oral colon-targeted drug delivery has gained popularity as an effective strategy for treatment of inflammatory bowel disease (IBD). In this study, we prepared colon-targeted dexamethasone microcrystals (DXMCs) coated with multilayers of chitosan oligosaccharide (CH), alginate (AG), and finally Eudragit S 100 (ES) (ES1 AG4 CH5 -DXMCs) using a layer-by-layer (LBL) coating technique. Particle size, surface charge, in vitro drug release, and in vivo anti-inflammatory activity of ES1 AG4 CH5 -DXMCs were evaluated. ES1 AG4 CH5 -DXMCs had an average particle size of 2.34 ± 0.19 μm and a negative surface charge of - 48 ± 9 mV. ES1 AG4 CH5 -DXMCs demonstrated pH-dependent dexamethasone release, avoiding initial burst drug release in acidic pH conditions of the stomach and small intestine, and providing subsequent sustained drug release in the colonic pH. Importantly, ES1 AG4 CH5 -DXMCs exhibited a significant therapeutic activity in a mouse model of colitis compared to other DXMCs. Overall, the LBL-coated DXMCs presented here could be a promising colon-targeted therapy for IBD.